Correlation of the inclination of the tentorium cerebellum and the volume of the posterior cranial fossa - Redžib Direković; Hakija Bečulić; Zdenka Krivokuća (Medicinski glasnik, 2023)
Aim: To investigate the influence of the inclination and insertion of the cerebellar tentorium on the posterior cranial fossa (PCF) volume. Methods: A retrospective, non-randomized study including 174 patients (117 females and 57 males) who underwent magnetic resonance imaging in the period from 31 December 2020 to 1 June 2021 under the indication (mostly headache) set by a competent ordinary. Acute or chronic intracranial events were not verified in the patients. Results: The average value of the PCF volume was 138.93 cm3 and the slope of the tentorium was 44.15°. Comparing the volume of the PCF and the slope of the tentorium in males and females no significant difference was found. A correlation was found in the females age groups 18-24 and 45-54 years. Conclusion: Understanding dimensions of the posterior cranial fossa morphometry has clear implications for reducing morbidity and mortality in surgery, especially in the case of applying lateral approaches and their variations.
Keywords: cerebellar malformation; posterior fossa capacity; tentorial position